Effects of a Rivastigmine Patch on Self-Care Activities in Patients with Alzheimer's Disease plus Cerebrovascular Disease - Kim, Yong Kyun (Dement Geriatr Cogn Dis Extra, 2014)
BACKGROUND/AIMS: In dementia patients, a deficit in activities of daily living (ADL) is one of the main problems. Our objective was to assess ADL using the Korean Modified Barthel Index (K-MBI) in patients with Alzheimer's disease (AD) plus cerebrovascular disease (CVD) treated with a rivastigmine patch for 24 weeks in an open-label, observational study. METHODS: 29 patients were enrolled who met the National Institute of Neurological and Communicative Disorders and Stroke/Alzheimer's Disease and Related Disorders Association (NINCDS/ ANDRA) criteria and had a score of 10-26 on the Korean version of the Mini-Mental State Examination (K-MMSE). After the rivastigmine patch had been applied for 24 weeks, changes in self-care activities were assessed using the K-MBI. RESULTS: The average age of the patients was 62.8 years, and they had an average K-MMSE score of 16.2. Patients showed a mean improvement of 21.9 points, as compared with the baseline K-MBI score of 30.3 (p < 0.05). Significantly better outcomes were seen in secondary outcome variables, for example the K-MMSE and backward digit span. The most frequent adverse events were skin problems, such as itching sensation (10%). CONCLUSION: In this multicenter, open-label, observational study, the rivastigmine patch was associated with improvements in ADL in patients with AD plus CVD.